MUMĀRASĀT ‘ADAM AL-IMTITHĀL AL-SHAR’I FĪ AL-BUNŪK AL-ISLĀMIYYA: Dirāsa li Arā’ Muwaẓẓifī al-Bunūk al-Islāmiyya al-Sābiqīn fī Indūnīsiyā (State Islamic University (UIN) of Sunan Ampel Surabaya, 2024)
The increasing trend of hijra in Indonesia since the last decade has had an impact on workers in the Islamic banking sector. Even though these workers are already working in Islamic financial institutions, not a few of them have resigned because they want to leave usury. This study aims to explore the views of members of the XBank community regarding Shariah non-compliance practices at Shariah banks, the causal factors, and their implications for these financial institutions. This study was conducted on former Islamic bank employees who resigned due to religious reasons and joined the Xbank community. Data was obtained through observation, in-depth interviews, and documentation. The findings of this study indicate that the resignation of workers in the Islamic banking sector is influenced by the many practices that violate sharia principles in the process of executing Islamic bank products. This sharia non-compliance was triggered by the low commitment of Islamic bank human resources to sharia principles and pressure from management to pursue bank profit targets. This sharia non-compliance has the potential to cause a decline in Muslim confidence in this Islamic financial institution.